Aalto open access fund pilot - Tiitinen, Kalle (Septentrio Conference Series, 2017)
At the start of 2017, an Open Access Fund Pilot was launched to support Aalto University’s researchers with the OA article payments (APC-charges). The Open Access Fund Pilot is the first and one of a kind in Finland. This poster discusses current results and best practices learned from managing an Open Access fund in Finland’s context. The poster also presents the fund’s workflows including, e.g., departments’ personnel, publishers’ APC discount programs and the Learning Centre (previously the Library). Aalto University has reserved 120 000 euros for the pilot. Every department has its own quota for OA article payments. The quota depends on the publishing activity of the department during the past few years. The head of department makes final decisions for the use of the department quota. In order to get the funding, publications must meet certain criteria. The pilot funds only the open access publishing of journal and conference articles. Both Gold and Hybrid OA journals’ APC costs are accepted. Furthermore, Publication Forum, a classification of publication channels created by the Finnish scientific community, is used as a part of funding criteria. The Publication Forum’s levels are 1 = basic, 2 = leading, and 3 = top, and fully OA journals must be rated 1, 2 or 3 and Hybrid-model journals 2 or 3 in order to get the funding. The Learning Centre verifies that the publication meets the requirements of the OAF-pilot and checks if there are any discounts on APC-charges. If the publication meets all the requirements of the OAF-pilot, Learning Centre guides the researcher to apply for funding for APC-charges. The Learning Centre is also responsible for communications and informing of the OAF-pilot and for monitoring departments’ quotas. Currently, we have 34 applications from which most have met the requirements of AOF-pilot. So far, the total amount of funding granted is 29 796 €.